If it's not what You are looking for type in the equation solver your own equation and let us solve it.
1=4(x-10)
We move all terms to the left:
1-(4(x-10))=0
We calculate terms in parentheses: -(4(x-10)), so:We get rid of parentheses
4(x-10)
We multiply parentheses
4x-40
Back to the equation:
-(4x-40)
-4x+40+1=0
We add all the numbers together, and all the variables
-4x+41=0
We move all terms containing x to the left, all other terms to the right
-4x=-41
x=-41/-4
x=10+1/4
| 2^3x=1000 | | x-1=4(x-10 | | x+2=70 | | 3(-8+3n)=-96 | | 8m-15=18 | | j4=7 | | (x+7)^2+1=0 | | 5n+9=7 | | 4x+2+3=13 | | 3–j=4 | | x^2+134=-2x-14 | | t23=2 | | 4+3t=-14 | | 0=3x^2-18x+23 | | 2(3y+3)-6y=6 | | 6o-16=7 | | 3n+n=24+12 | | t2=26 | | 23t=2 | | 11=b/4+9 | | 8.2(6x-3)=7(2x-1.2) | | (5y+43)=54 | | 8.2(6x-3)=7(2x-1.2 | | 7w-7=0 | | t+23=2 | | (1+4x)(2x+5)=90 | | -r+-5=-10 | | s−81=8 | | 2x-(4-2)+7=30x= | | 5y+43=54 | | 9s+3=48 | | -3+4q=9 |